The level and forms of verbal creativity of microteaching student practitioners - Sufanti, Main; Wahyudi, Agus Budi; Fatimah, Nuraini; Purnomo, Eko; Noviana, Sinta Tri; Noviafitri, Kartika Satya; Utomo, Ammar Faqih (Universitas Ahmad Dahlan, 2025)
This study aims to describe the verbal creativity of student practitioners in the Microteaching course. The aspects discussed include verbal creativity based on the categories of flexibility, fluency, originality, and elaboration. Each category is described based on the level of scores (high or low) and the corresponding forms. The results of this study show that: (a) the level of fluency of students in generating many ideas is highest in word production. The forms of word production in the fluency category, based on the most frequently produced word classes, are nouns. Based on word meaning, most students tend to produce denotative meanings. This reflects a tendency to use words in their general or literal sense. (b) the level of flexibility of microteaching student practitioners is high. In terms of form, student practitioners demonstrate high flexibility in sentence form and sentence use, but lower in sentence length, imagination, and fantasy. (c) the level of originality of microteaching student practitioners is high. The forms of students’ verbal creativity originality include five aspects: originality in theme, original solution or ending, humorous elements in sentences, the use of self-created words or names, and the originality of the respondent’s writing style. (d) the level of elaboration of student practitioners is high. Meanwhile, the forms of elaboration include four aspects: aesthetic quality, emotional content, empathy, and personal elements, while the elements of direct narrative sentence conversation and the use of quotations are not fulfilled.